About the non-consistency of PTV-based prescription in lung. (December 2017) - Lebredonchel, S.; Lacornerie, T.; Rault, E.; Wagner, A.; Reynaert, N.; Crop, F.
Highlights: Shows inconsistency of prescribing to lung PTV volumes for Monte Carlo calculations. Provides data showing that Dose Mass Histograms do not offer a solution either. The suggested solution is to abandon the PTV concept. Abstract: Purpose: The goal of this study is to show that the PTV concept is inconsistent for prescribing lung treatments when using type B algorithms, which take into account lateral electron transport. It is well known that type A dose calculation algorithms are not capable of calculating dose in lung correctly. Dose calculations should be based on type B algorithms. However, the combination of a type B algorithm with the PTV concept leads to prescription inconsistencies. Methods: A spherical isocentric setup has been simulated, using multiple realistic values for lung density, tumor density and collimator size. Different prescription methods are investigated using Dose-Volume-Histograms (DVH), Dose-Mass-Histograms (DMH), generalized Equivalent Uniform Dose (gEUD) and surrounding isodose percentage. Results: Isodose percentages on the PTV drop down to 50% for small tumors and low lung density. When applying the same PTV prescription to different patients with different lung characteristics, the effective mean dose to the GTV is very different, with factors up to 1.4. The most consistent prescription method seems to be the D 50 % DMH (PTV) DMH point, but is also limited to tumors with size over 1 cm. Conclusions: Even when using the different prescription methods, the prescription to the PTV is not consistent for type B-algorithm based dose calculations if clinical studies should produce coherent data. This combination leads to patients' GTV with low lung density possibly receiving very high dose compared to patients with higher lung density. The only solution seems to remove the classical PTV concept for type B dose calculations in lung.